Ordered Macroporous Superstructure of Nitrogen‐Doped Nanoporous Carbon Implanted with Ultrafine Ru Nanoclusters for Efficient pH‐Universal Hydrogen Evolution Reaction - Wu, Yu‐Lin; Li, Xiaofang; Wei, Yong‐Sheng; Fu, Zhaoming; Wei, Wenbo; Wu, Xin‐Tao; Zhu, Qi‐Long; Xu, Qiang (Advanced materials (Weinheim), 2021)
The electrochemical hydrogen evolution reaction (HER) is an attractive technology for the mass production of hydrogen. Ru‐based materials are promising electrocatalysts owing to the similar bonding strength with hydrogen but much lower cost than Pt catalysts. Herein, an ordered macroporous superstructure of N‐doped nanoporous carbon anchored with the ultrafine Ru nanoclusters as electrocatalytic micro/nanoreactors is developed via the thermal pyrolysis of ordered macroporous single crystals of ZIF‐8 accommodating Ru(III) ions. Benefiting from the highly interconnected reticular macro–nanospaces, this superstrucure affords unparalleled performance for pH‐universal HER, with order of magnitude higher mass activity compared to the benchmark Pt/C. Notably, an exceptionally low overpotential of only 13 mV@10 mA cm−2 is required for HER in alkaline solution, with a low Tafel slope of 40.41 mV dec−1 and an ultrahigh turnover frequency value of 1.6 H2 s−1 at 25 mV, greatly outperforming Pt/C. Furthermore, the hydrogen generation rates are almost twice those of Pt/C during practical overall alkaline water splitting. A solar‐to‐hydrogen system is also demonstrated to further promote the application. This research may open a new avenue for the development of advanced electrocatalytic micro/nanoreactors with controlled morphology and excellent performance for future energy applications. An ordered macroporous superstructure of nitrogen‐doped nanoporous carbon implanted with ultrafine Ru nanoclusters is developed via thermal pyrolysis of the ordered macroporous single crystals of ZIF‐8 accommodating Ru(III) ions, which affords unparalleled performance for the pH‐universal hydrogen evolution reaction, with order of magnitude higher mass activity compared to the benchmark Pt/C.